Is there a relation between dental calculus and kidney stone? - Yildirim, Kadir; Yildirim, Tuba Talo; Kaya, Filiz Acun (My University, 2021)
Aim: The purpose of this research is to investigate the frequency of dental calculus in patients with kidney stone and without kidney stone. Methodology: Two hundred eighty-seven patients (143 men and 144 women) aged between 18 and 68 (mean age 38.38±13.74) were included in the study. Patients were divided two groups in which 143 subjects without kidney stones (group I) and 144 subject with kidney stones (group II). Intragroup and inter-group analyzes were performed in terms of periodontal status and dental calculus index according to educational level, frequency of toothbrushing and smoking. Results: The study sample consisted of 287 patients which 143 in group I, 144 in group II. The mean age of the group I was 36.77±12.81 years old, and group II was 39.98±14.47 years old. There was a statistically significant difference between periodontal status and education level, daily tooth brushing and smoking in group I and group II (p<0.05). Both in group I and group II there was a statistically significant difference periodontal calculus index and education level, smoking, daily tooth brushing (p<0.05). In addition, there were significant correlations between dental calculus index and size of the kidney stone. Conclusion: There is a significant difference between the groups in terms of dental calculus index. There is a need for additional study on this subject in the future.
Keywords: Diş Hekimliği